Exploring Perceptions of Curriculum Change in Initial English Language Teacher Education: A Case in Argentina - Darío Luis Banegas (Universidad de Navarra, 2016)
With the implementation of a new national education law in Argentina, the theoretical underpinnings, structure, and knowledge base for initial teacher education are being transformed. In the province of Chubut, southern Argentina, 2014 was devoted to the delineation of new jurisdictional programmes (Banegas, 2014), and 2015 was the year of implementing such programmes. In this paper I examine the perceptions of a group of students at an initial English language teacher education (IELTE) programme who decided to transfer from their 2013 cohort to the 2015 cohort under the new programme. I also examine teacher educators' perceptions of the new programme. Through both students' and teacher educators' views, I compare and contrast the strengths, weaknesses and challenges of the changes introduced in IELTE in my context.